Association between Clinical Pathway for Cesarean Section and Length of Stay in Dr. Saiful Anwar Regional Hospital Malang - Rusfandi, Annisa Adhania; Agung Indrawan, I Wayan (Fakultas Kedokteran Universitas Brawijaya, 2025)
Cesarean section (C-section) is one of the main medical procedures performed at Dr. Saiful Anwar Regional Hospital in Malang. Implementing a clinical pathway (CP) as a standard of evidence-based care can influence the length of hospital stay for patients. This study aims to analyze the relationship between CP implementation and the length of hospital stay for C-section patients at Dr. Saiful Anwar Regional Hospital. The analysis was based on data from CP forms and patient medical records. The lowest CP implementation score in this study was 89.86%. A correlation test across all samples (n=97) revealed a significant relationship between CP implementation and length of stay (correlation coefficient: 0.246, p=0.008). Dividing the samples into four groups based on the most frequent diagnosis categories (placenta previa, PROM (Premature Rupture of Membranes), preeclampsia, and placenta accreta) showed significant differences in the length of stay between patients with PROM and those with preeclampsia (p=0.0001) and placenta accreta (p=0.002). The CP implementation rate for all C-section patients was above 80% and was significantly correlated with the length of hospital stay. In the future, CPs specifically designed for different C-section indications may be developed to accommodate various patient conditions.